Parapagus (dicephalus, tetrabrachius, dipus) conjoined twins and their rehabilitation - Başaran, Sibel; Güzel, Rengin; Keskin, Erbuğ; Sarpel, Tunay (The Turkish Journal of Pediatrics, 2013)
A case of female parapagus conjoined twins living as unseparated is presented in this report. The twins had two heads, four arms and two legs. As a result of their fusion, operative care had been considered to be unacceptable, and the family had refused to take care of them. At three years of age, they were referred to the Rehabilitation Department with the complaint of inability to walk. While designing the rehabilitation program, somatosensory evoked potential evaluation was performed and showed that twin 1 controlled the right leg and twin 2 controlled the left. The program consisted of coordinated pacing training by verbal commands, upper and lower extremity reeducation, and balance and coordination exercises. After two months of inpatient rehabilitation, they were able to walk independently with a specially designed walker. Currently, the twins are 11 years old with normal academic achievement, and they are able to walk, run and climb the stairs independently.